ANALISIS PENGUKURAN WAKTU KERJA PENGOLAH DATA REGSOSEK SERVER 3 BADAN PUSAT STATISTIK SURABAYA DENGAN METODE WORKLOAD ANALYSIS - Nurun Nadhif; Handy Febry Satoto (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Workload is a process or activity that must be completed by a worker within a certain period of time. If a worker is able to complete and adapt to a given number of tasks, then this does not become a workload. However, if the worker is not successful then the tasks and activities become a workload. Workload itself is one of the important factors that must be considered by the company in managing human resources. Excessive workload can cause stress and fatigue which can have an impact on employee performance in the company. Based on observations and interviews there were several periods when operators could not meet data entry targets, this happened because they worked under constant pressure so that some operators experienced work stress. With the problems that occur, this research will be carried out by calculating the analysis of work time and mental workload on the workforce in order to optimize the workforce. This type of research uses the Work Sampling method to obtain a total average time for data input process of 3.35 minutes taking into account the Performance Rating and the Allowance value. The NASA – TLX method results in the majority of the workforce having high workload scores. The value of high mental workload is 79 on operator 11 (Choirul Ashari). As well as the results of the Workload Analysis method, it results that the input data input operator experiences a high workload with a workload range of 26% - 96%.